Marqueurs de discours et distanciation: une étude contrastive de Peut-être, capaz et por ahi - Garcia Negroni, Maria Marta (2013)
In this paper, the semantic function of French peut-être and two typical markers of the Spanish of the Rio de la Plata, capaz and por ahi, are described in a contrastive way. While these three markers can generally introduce the speaker’s distance from his or her discourse, our corpus shows that three general categories of use must be distinguished: attenuation, sharper distance and radical rejection of the viewpoint so marked. In the framework of a polyphonic and argumentative semantics, a corpus of dialogical and monological speech, be it French or Spanish, is analysed.